(untitled) (International Journal of Engineering and Computer Science, 2013)
Minimum Spanning Network Connectivity possesses self adaptcity. In order to construct telecommunications, wireless communications, routing is one of the key challenging issues to be addressed. In this paper, A new Algorithm for Minimum Spanning Network Connectivity is proposed. This algorithm is proposed based on the Pandit’s approach. Proposed new algorithm incorporates with drainage system in a city, Vehicle routing, Linked with different rivers etc. Thus new algorithm aims to choose optimal minimum spanning network connectivity from nodes to the destination. This algorithm is compared with previously suggested algorithms to performance differences. Extension experimental evaluations are performed from suitable numerical example. It is shows that the new algorithm for minimum spanning network connectivity provides better than the previously suggested algorithms.